Application of Flipped Classroom Method for Learning Worksheets Material - Irene Kim Lie; Rousilita Suhendah (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2023)
Based on data from the Central Bureau of Statistics, Indonesia is projected to enjoy a demographic bonus in 2045. This condition must be utilized because this is the first time in the history of the Indonesian nation. The demographic bonus that will occur in 2045 should be utilized properly. One is education that supports the younger generation to be more innovative, intelligent, critical-thinking, and skilled. The skills that a student can possess are in the field of accounting. Besides building skills, accounting can also shape the way of critical thinking and add focus and thoroughness to a student. St. Kristoforus 1 High School, as one of the target schools, has several students still interested in accounting. Due to this enthusiasm, Universitas Tarumanagara was there to provide accounting training, and the method chosen was the flipped classroom method. This paper explains the working paper where the general use is to help the process of making financial statements. Each educator will get the learning material first, so there is a difference between the conventional type of learning that usually occurs when exploring the material. This method was chosen because it is suitable to support the understanding of accounting materials and it can explore the material to be discussed more widely. This training is expected to be used by students to open a business in the future or continue their education at a higher level.